The securitization markets handbook : structures and dynamics of mortgage- and asset-backed securities - Stone, Charles A. (Charles Austin) (Wiley finance series., 2012)
A comprehensive guide to the continuously evolving world of securitization The Second Edition of The Securitization Markets Handbook is a valuable resource for both experienced money managers trying to put a securitization strategy into place as well as newcomers looking to acquire a broad and strong foundation in this discipline. This edition takes a close look at the pre- and post-crash mortgage market and the mortgage-backed securities based on those mortgages, as well as other asset-backed securities including commercial paper or credit cards.